Upaya Meningkatkan Hasil Belajar IPA dengan Menggunakan Model Pembelajaran Artikulasi Berbantuan Media Visual pada Peserta Didik Kelas IV SDN 5 Panarung Palangkaraya Tahun Pelajaran 2017/2018: Efforts to Improve Science Learning Outcomes by Using Visual Media Assisted Articulation Learning Model in Class IV Students of SDN 5 Panarung Palangkaraya 2017/2018 Academic Year - Metri Satriani; Muhamad Ramli (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to find out the science learning activities of fourth grade students of SDN 5 Panarung by applying the articulation model assisted by visual media and improving the learning outcomes of science students of fourth grade SDN 5 Panarung by applying an articulation model supported by visual media on the material impact of natural materials on environmental conservation in the fourth grade of SDN 5 Panarung Palangkaraya. The type in this study was to use the kind of Classroom Action Research (CAR). As for the subjects of this study were the fourth grade students of SDN 5 Panarung which numbered 27 students. The instrument used in this study was in the form of observation sheets and test questions in the way of multiple choice learning outcomes. The data analysis technique used is qualitative and quantitative. From the results of the study concluded that: (1) Learning activities of students appear active in learning science in the application of articulation models assisted by visual media. Students play an active role during the learning process in cycle I. The results of observations of student activities are 3.52 with very busy criteria, and (2) There is an increase in student learning outcomes after the application of articulation models assisted by visual media. This is indicated by the learning outcomes seen through the class average score in the first cycle, which is 79 with the criteria achieved and fulfilling the KKM 70, reaching the percentage of students' classical mastery learning, namely 100%, with 85% artistic completeness.